2023
DOI: 10.1002/nop2.1591
|View full text |Cite
|
Sign up to set email alerts
|

Action research on promoting hand hygiene practices in an intensive care unit

Abstract: Aim Evaluate the intensive care acquired infections incidence and the change over time in infection practices in one intensive care unit. Design We used an action research approach with cyclical activities. Methods Our study included two cycles with hand hygiene observation based on the WHO's five‐moments observation tool, observing hand hygiene practices, analysing the observations, and giving feedback on observations, intensive care acquired infection rates, and alcohol‐based hand rub consumption. The Revise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
0
0
Order By: Relevance
“…Despite the existence of standardized protocols for invasive procedures in the ICU, such as various types of intubation, adherence to these protocols is not always consistent among staff members. Previous studies have highlighted suboptimal rates of hand hygiene compliance among ICU medical staff, inadequate adherence to maximum sterile barrier precautions for central venous catheters, and the need for improved training, supervision, and feedback [7][8][9]. Consequently, experts have suggested that strengthening training in nosocomial infection knowledge is necessary to enhance in-hospital infection management [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of standardized protocols for invasive procedures in the ICU, such as various types of intubation, adherence to these protocols is not always consistent among staff members. Previous studies have highlighted suboptimal rates of hand hygiene compliance among ICU medical staff, inadequate adherence to maximum sterile barrier precautions for central venous catheters, and the need for improved training, supervision, and feedback [7][8][9]. Consequently, experts have suggested that strengthening training in nosocomial infection knowledge is necessary to enhance in-hospital infection management [10].…”
Section: Introductionmentioning
confidence: 99%